2015
DOI: 10.14260/jemds/2015/1973
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in Pregnancy and Its Impact on Maternal and Fetal Outcome

Abstract: Thyroid disorders are most common endocrine disorders affecting women of reproductive age group Hypothyroidism is common in pregnancy with an estimated prevalence of 2-3% Maternal hypothyroidism leads to many maternal and perinatal complications like miscarriage, gestational diabetes mellitus, pre-eclampsia, pre-term labor, placental abruption and fetal death. AIMS AND OBJECTIVE: To find out the effect of hypothyroidism on the course of pregnancy, to study the neonatal outcome, to know the prevalence of subcli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A total of 4808 patients with subclinical hypothyroidism, 94306 with euthyroidism, and the rest with other thyroid diseases [there is a part of the repeated population because Li, M.F., et al. and his colleagues assessed the same population with different diagnostic criteria, respectively ( 10 )].There were 15 prospective cohort studies ( 16 20 , 22 29 , 31 , 32 ) and 7 retrospective cohort studies ( 4 , 7 , 10 , 11 , 21 , 30 , 33 ). In addition, due to slight differences in thyroid parameters during different pregnancy periods, there were 10, 6, and 1 studies evaluating the relationship between subclinical hypothyroidism in pregnancy and HDP in the first, second, and third trimesters, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4808 patients with subclinical hypothyroidism, 94306 with euthyroidism, and the rest with other thyroid diseases [there is a part of the repeated population because Li, M.F., et al. and his colleagues assessed the same population with different diagnostic criteria, respectively ( 10 )].There were 15 prospective cohort studies ( 16 20 , 22 29 , 31 , 32 ) and 7 retrospective cohort studies ( 4 , 7 , 10 , 11 , 21 , 30 , 33 ). In addition, due to slight differences in thyroid parameters during different pregnancy periods, there were 10, 6, and 1 studies evaluating the relationship between subclinical hypothyroidism in pregnancy and HDP in the first, second, and third trimesters, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We then further searched the full texts of 40 articles to assess their eligibility, of which 15 were case-control studies, 2 studies were poorly defined for disease, and 2 studies that did not provide HDP-related data were excluded. Eventually, we included 22 original studies to investigate the relationship between subclinical hypothyroidism in pregnancy and HDP (7,10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). (10)].…”
Section: Search Resultsmentioning
confidence: 99%
“…Hypothyroidism was also found to be a major cause of miscarriage in some studies, but in our study, we did not observe much variations in adversity among the group comparatively. [ 15 , 16 ] Whereas a prospective study on elderly pregnant (>35 years) women belonging to the western part of India has found a significantly higher proportion of maternal and fetal mortality and morbidity among them. Antenatal and intranatal complications were increased in their study group along with an increased incidence of LBW babies compared to the comparison group (40.20% vs. 24%).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Thus presence of thyroid autoantibodies can cause dysregulated activity of immune system at fetal-maternal interface causing abortions and preterm labour. 15 Ruchi Kishore et al studied about fetal outcome in hypothyroid women and concluded that 6.2% were IUD and 13% were IUGR in hypothyroid patients. 16 In present study, fetal outcome was; IUGR 3.3% and 1.3% cases of IUD.…”
Section: Discussionmentioning
confidence: 99%